Investigation of selective binding of inhibitors to PTP1B and TCPTP by accelerated molecular dynamics simulations. Issue 14 (22nd September 2019) - Chen, Xi; Gan, Qiang; Feng, Changgen; Liu, Xia; Zhang, Qian
Abstract: Protein tyrosine phosphatase 1B (PTP1B), a key negative regulator in insulin signaling pathways, is regarded as a potential target for the treatment of type II diabetes and obesity. However, the mechanism underlying the selectivity of PTP1B inhibitors against T-cell protein tyrosine phosphatase (TCPTP) remains controversial, which is due to the high similarity between PTP1B and TCPTP sequence and the fact that no ligand–protein complex of TCPTP has been established yet. Here, the accelerated molecular dynamics (aMD) method was used to investigate the structural dynamics of PTP1B and TCPTP that are bound by two chemically similar inhibitors with distinct selectivity. The conformational transitions during the "open" to "close" states of four complexes were captured, and free energy profiles of important residue pairs were analyzed in detail. Additional MM-PBSA calculations confirmed that the binding free energies of final states were consistent with the experimental results, and the energetic contributions of important residues were further investigated by alanine scanning mutagenesis. By comparing the four complexes, the different conformational behavior of WPD-loop, R-loop, and the second pTyr binding site induced by inhibitors were featured and found to be crucial for the selectivity of inhibitors. This study provides new mechanistic insights of specific binding of inhibitors to PTP1B and TCPTP, which can be exploited to the further structural-based inhibitor design. Communicated by Ramaswamy H. Sarma